2007
DOI: 10.1128/jvi.02562-06
|View full text |Cite
|
Sign up to set email alerts
|

Functional Effects of Coxsackievirus and Adenovirus Receptor Glycosylation on Homophilic Adhesion and Adenoviral Infection

Abstract: The coxsackievirus and adenovirus receptor (CAR) is both a viral receptor and homophilic adhesion protein.The extracellular portion of CAR consists of two immunoglobulin (Ig)-like domains, each with a consensus sequence for N-glycosylation. We used chemical, genetic, and biochemical studies to show that both sites are glycosylated and contribute to the function of CAR. Although the glycosylation of CAR does not alter cell surface levels or junctional localization, it affects both adhesion and adenovirus infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 31 publications
4
26
0
Order By: Relevance
“…In contrast, glycosylation appears to inhibit PV binding to PVR (16,26). CAR has two glycosylation sites, one on each extracellular domain (38). He et al (7) observed that a CAR-D1 domain, produced in bacteria and therefore lacking glycosylation, bound poorly to CVB3 (7), and other authors (38) have suggested that this might indicate a role for glycosylation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, glycosylation appears to inhibit PV binding to PVR (16,26). CAR has two glycosylation sites, one on each extracellular domain (38). He et al (7) observed that a CAR-D1 domain, produced in bacteria and therefore lacking glycosylation, bound poorly to CVB3 (7), and other authors (38) have suggested that this might indicate a role for glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…CAR has two glycosylation sites, one on each extracellular domain (38). He et al (7) observed that a CAR-D1 domain, produced in bacteria and therefore lacking glycosylation, bound poorly to CVB3 (7), and other authors (38) have suggested that this might indicate a role for glycosylation. However, we found that deglycosylation of the D1 and/or D2 domains of CAR had no adverse effect on CVB3 binding or infec- , and an intracellular domain (ICD).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Horseradish peroxidase-labeled secondary antibodies were from Jackson ImmunoResearch (West Grove, PA). Rabbit anti-CAR-1605 and anti-CAR Ex8 -5678 have previously been described (10,11,14,28 (42). For Fluorescence Resonance Energy Transfer (FRET) and binding assays, MAGI-1 PDZ1, PDZ2, and PDZ3 domains and the CAR Ex8 C terminus were cloned (In-Fusion; Clontech) into a pGEX-6p vector (GE Healthcare, Piscataway, NJ) modified to contain a His tag upstream of the glutathione transferase (GST) tag (pHH2).…”
Section: Methodsmentioning
confidence: 99%
“…The JAM family of proteins has been categorized as belonging to the tight junction, but we classify these proteins as part of the adherens proteins because they are located inferior to the tight junctions (4). We have found that opening the tight junctions with EDTA greatly enhances adenovirus and reovirus interactions with CAR (13). Anchoring proteins, such as cingulin, link JAM proteins to the actin cytoskeleton via their PDZ-binding domain.…”
Section: Adherens Junctionsmentioning
confidence: 99%